Effect of Heat Input on Micro-Hardness and Shear Strength of Inconel 625 Hardfacing onto AISI 347 Steel pipes by GMAW Process. (November 2019) - Rajkumar, V.; Arjunan, T.V.; Vasan, Adithya; Rajesh, Kannan A
Abstract: Inconel 625 is one of the most accepted hardfacing material having good corrosion resistance properties at high temperature applications. Hardfacing is the deposition of a hard surface layer to the base metal by means of welding. The benefit of hardfacing is resistance to environmental stresses mainly corrosion at elevated temperatures. Thermal input plays a critical role for manufacturing good hardfaced components with respect to weld bead geometry, cooling rate, etc. In the present study, an L9 orthogonal array of input parameters were carried out with different heat input combinations using 98% Argon + 2% CO2 as shielding gas. Single layer hardfacing was done. The bead-on-pipe welding trials and macroscopic analysis were carried out to find the optimal welding parameters that yielded minimum dilution. The hardfaced layer thickness varies from 1.88mm to 2.58mm on substrate following optimum welding parameters. Visual inspection results reveal that most of welds of higher heat input conditions possess good quality. It is visually observed that width of weld increases with increase in welding heat input. It is noticed that in the range of 200-250 mm/min welding speed and 150A of welding current, good reinforcement and weld bead width at optimum penetration is observed in the experiments. Shear strength test and micro-hardness test were performed over test samples prepared from hardfaced part. Results revealed that both micro-hardness and shear strength of the hardfaced layer were more than that of base metal and values of both increased with increase in heat input. The Inconel 625 hardfaced layer exhibited 32 % higher hardness than the substrate material AISI 347.